Coping with poachers in European stalked barnacle fisheries: Insights from a stakeholder workshop. (January 2022) - Geiger, Katja J.; Rivera, Antonella; Aguión, Alba; Álvarez, Jorge; Arrontes, Julio; Borrell, Yaisel Juan; Cruz, Teresa; Davoult, Dominique; Dubert, Jesús; Feis, Marieke E.; Fernandes, Joana N.; Fernández, Consolación; et al.
Abstract: In January 2020, a stakeholder workshop was organized as a knowledge sharing strategy among European stalked barnacle fisheries. Management of this fishery differs greatly among regions and ranges from less organized and governed at large scales (>100 km, coasts of SW Portugal and Brittany in France) to highly participatory systems which are co-managed at small spatial scales (10′s km and less, Galicia and Asturias). Discussions revealed that poaching is ubiquitous, hard to eradicate, and adapts to all types of management. The stakeholders identified some key management initiatives in the fight against poaching: granting professional harvesters with exclusive access to the resource, increasing social capital among harvesters through tenure systems (e.g. Territorial Use Rights in Fisheries) that empower them as stewards of their resource and intensification of surveillance with the active participation of the harvesters. Furthermore, increased cooperation between fishers associations and regional fisheries authorities, improved legal frameworks, adoption of new technologies and the implementation of market-based solutions can also help coping with this systemic problem.